Poorly differentiated adenocarcinoma manifesting as multifocal obstructive disease -a rare occurrence - Sathe, Pragati Aditya; Chaudhari, Jayashri Popat; Karegar, Manjusha Milind; Mirjolkar, Amit Suresh (Annals of Pathology and Laboratory Medicine, 2018)
We describe an autopsy of a very unusual case of an adult female presenting with multifocal obstructive symptoms like achalasia, obstructive jaundice and bilateral hydronephrosis . Primary clinical diagnosis was tuberculosis and malignancy. Although the patient was extensively worked up in the hospital with multiple biopsies, the diagnosis could not be made. Autopsy revealed contiguous involvement of entire gastrointestinal tract from esophagus till colon by a poorly differentiated adenocarcinoma with diffuse thickening, firmness and rigidity of the wall. The tumor cells were focally expressing CK 20 favouring a colonic primary. Colonic adenocarcinoma usually spread by either lymphatic or hematogenous way to lymph nodes, liver and lung. This unusual way of spread of this tumor contiguously from colon till esophagus, with Urinary bladder and distal CBD infiltration make it very unique. DOI:10.21276/APALM.1757